An Investigation of Factors Contributing to Job Stress for Secondary School Teachers in Kota Samarahan, Sarawak - Dayang Rosaida Abang Madni; Noni Harianti Junaidi (RIRAI Publisher, 2022)
Being a teacher had been recognized as a stressful job. Teachers had experienced stress due to several factors such as workload(s), students’ behavior, administration support, and working environment. The objective of this study is to identify the level of work stress among secondary school teachers. The significance of this study will be able to help increase awareness that teachers may suffer from work stress. The research objectives were answered using descriptive analysis, Pearson correlation, and multiple regression analysis. This study used a survey questionnaire method to collect data. The respondents of this study consisted of 158 teachers from two secondary schools in Kota Samarahan. A simple random sampling method was used to select the sample and data was analyzed by using the Statistical Package of Social Sciences (SPSS). The findings of this study revealed that secondary school teachers were experiencing a medium level of work stress. It was also found that all the independent variables comprised of workloads, students’ behavior, administrative support, and working environment have a positive medium relationship with the level of work stress. Finally, it was found that student behavior is the major factor contributing to work stress among teachers.